500 OPTICAL COHERENCE TOMOGRAPHY AND IMAGE ANALYSIS OF THE OROPHARYNX. (1st January 2005) - Ridgway, J.; Mahmood, U.; Jackson, R.; Guo, S.; Su, J.; Armstrong, W.; Shibuya, T.; Crumley, R.; Chen, Z.; Wong, B.
Abstract : Introduction: Diagnostic characterization of oropharyngeal pathology has been limited by the spatial resolution of current imaging modalities including CT, MRI, and Ultrasonography. One promising technology that allows for in vivo microstructure characterization is Optical Coherence Tomography (OCT). Current research and advances in OCT outside the medical fields of ophthalmology, cardiology, and gastroenterology has revealed the value of this modality in analysis of the adult human upper aero-digestive tract. Methods: Significant progress has been made within our laboratory in the development and application of a high-speed, high resolution, real-time OCT imaging system that is used in the assessment of in vivo imaging of oropharyngeal tissue in adult patients. This non-contact, non-invasive diagnostic tool combines a broadband light source and interferometry to produce high-resolution cross-sectional images (8–20µm) in biologic tissues. Results: High-resolution images of tissue microstructure, surrounding tissues, and tissue layer boundaries was performed in fifty adult patients characterizing an array of normal, benign, and pathologic conditions. Conclusion: Preliminary information of in vivo adult oropharyngeal tissues will be presented in addition to modifications of current instrumentation to accommodate the oropharynx. Highlights of other applications will be reviewed as our study broadens its analysis of the variable and complex disorders in the pediatric population.